PENANGGULANGAN KEMISKINAN - Syaripulloh Syaripulloh (Jurnal Dialog, 2017)
Poverty is a very complex development issues. Poverty is seen as spillovers from development and part of the problem in development. The existence of poverty is characterized by unemployment, underdevelopment, and inequality between regions. Poverty is also indicated by the presence of slums and squatter, and the existence of groups of people categorized as poor families caused by the limitations of economic, social and political life of their poor families. This phenomenon is demonstrated by the presence of several heads of families who are economically unable to meet the primary needs of family members. In addition, low levels of public education also makes it difficult to obtain jobs with adequate results or provide for his family. There are also a number of families whose low level of health that is hindering their work. This paper would like to discuss the steps that can be taken by the government to tackle poverty masalahan. KEY WORDS:Poverty, Unemployment, Underdevelopmen, Inequality, Poor Family, Low Level of Education.